Sulfur‐Implanted Carbon Dots‐Embedded Graphene as Ultrastable Anode for Li‐Ion Batteries. Issue 2 (12th January 2021) - Gottam, Ramesh; Zhang, Xiangxin; Chen, Jiang; Xue, Xilai; Zhang, Yining
Abstract : Sulfur doping in carbonaceous materials is an effective approach to improve the performance of Li‐ion batteries (LIBs). Herein, sulfur‐implanted carbon dots‐embedded graphene (S‐CDs/rGO) as an anode material for LIBs is reported. A facile method is used to prepare S‐CDs/rGO by annealing the mixture of benzyl disulfide (BDS) and graphene oxide (GO). Herein, BDS serves as both the sulfur source and precursor of CDs. S‐CDs/rGO as an anode material for LIB delivers initial specific capacities of 938.8 mAh g −1 (first cycle) and 598.6 mAh g −1 (second cycle) at a current density of 100 mA g −1 . S‐CDs/rGO exhibits superior cycling performance with good capacity retentions of 78.8% (500 cycles), 61.5% (2000 cycles), and 75.7% (2000 cycles) at higher current densities of 1000, 2000, and 3000 mA g −1, respectively. Moreover, the full cell assembly of the prepared S‐CDs/rGO as an anode and commercial LiFePO4 as a cathode in the voltage range of 1.5–3.9 V delivers a high reversible capacity of 203.3 mAh g −1 after extensive 1000 cycles at 500 mA g −1 with 51.8% retention (a low fading rate of 0.049% per cycle), rendering it as a promising anode material for application in high‐performance LIBs. Abstract : Sulfur‐implanted carbon dots (S‐CDs) improve the specific capacity and cycling stability of rGO as anode material for LIBs. Moreover, the full cell assembled with the prepared S‐CDs/rGO as anode and commercial LiFePO4 as cathode exhibits good rate capabilities and excellent cycling performance (a low fading rate of 0.049% per cycle) in a voltage range of 1.5–3.9 V.